Aplicación de alfaarbutina y niacinamida con técnica de microneedling para reducir lentigos solares en el rostro en paciente femenina de 53 años - Moreno Moreno, Janina Gabriela (2025)
The objective of this integrative project was to apply a protocol to reduce solar lentigines on the face, using the microneedling technique with niacinamide and alpha - arbutin, verifying its effectiveness through 12 sessions, alternating the active ingredients used. The study developed is of a descriptive - explanatory type with design - action, carried out on a 54-year-old female patient. This made it possible to evaluate the changes, during the time the treatment lasted. The main techniques used were patient evaluation, hygienization, collagen induction therapy (microneedling), repairing mask, moisturizing cream and sunscreen, using microneedling as an appliance and niacinamide and alpha-arbutin as active ingredients. The use of two active ingredients made it possible to verify the extent of the active ingredients. When applied in a specific area that is exposed to the sun and produces solar lentigines, it is challenging to remove them, so it is generally observed in people who are directly exposed to the sun and do not use sunscreen. In most cases, this problem causes a negative self-perception and low self-esteem. For this reason, the patient came for a consultation in search of a minimally invasive solution that would not prevent her from carrying out her daily activities. At the end of the programmed sessions, a significant reduction in the intensity of the lentigines was obtained, so combining these two active ingredients had a positive effect.